Design of Accounting Information System for Cooperative Savings and Loans Unit as Building Stakeholder Trust on Cooperative Management (A Case Study: Sari Rejeki Farmer Group Cooperative in Karanganyar) - Andi Asrihapsari; Vidia Ayu Satyanovi; Lina Nur Ardilla; Sri Hanggana; Sri Murni; Santoso Tri Hananto; Muhammad Syafiqurrahman; Renata Zoraifi (ITB AAS INDONESIA, 2022)
This study aims to develop an accounting information system design for the Savings and Loan Unit of Sari Rejeki Farmer Group Cooperative as a building stakeholder trust for cooperative management. This goal is achieved with the output in the form of a standard operating procedure document for the Savings and Loan Unit of the cooperative, which is designed using Microsoft Visio and Microsoft Word applications in realizing accountability. This study has applied descriptive qualitative research, which describes the object according to the existing conditions. The research data were gathered through case studies, observations, interviews, and literature studies. The structured systems analysis and design for system development were applied in the analysis and system design stages. To complete the steps of structured system development, tools and techniques were required. The tools for system development include pictures, diagrams, or graphs, while act finding was used for the technique. The cooperative accountability was assessed based on the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 13 of 2015 concerning the implementation of cooperative accountability. The results of this study indicate that the Savings and Loans Unit of Sari Rejeki Farmer Group Cooperative has met the indicators of accountability from the financial aspect, which covers the availability of clear information, transparency, implementation of accounting information systems in the application of SOPs for raising funds and SOPs for disbursing funds that have been properly and adequately integrated. Keywords: accounting information system, standard operating procedure, cooperative savings and loan unit